Optimizing Non-Antibiotic Treatments for Patients with Acne: A Review. Issue 4 (December 2016) - Canavan, Theresa; Chen, Edward; Elewski, Boni
Abstract Acne is a very common non-infectious skin condition that is frequently treated in dermatological practices. Because acne is often chronic and may persist for years, safe and effective long-term maintenance therapy is often required. Given the increasing frequency of antibiotic-resistant bacteria and the gravity of the consequences of this trend, it behooves dermatologists to maximize use of non-antimicrobial therapy when treating acne. In this review of the literature we present data regarding the efficacy and appropriate use of non-antimicrobial treatments for acne. A variety of topical and oral treatment options exist that can be used in a step-wise manner according to the patients' severity and therapeutic response. Non-antimicrobial treatments can be highly efficacious at controlling acne, especially when used as maintenance therapy. While antibiotics have a role in acne treatment, they should not be used as monotherapy, and lengthy courses of antibiotic use are discouraged.